Analysis of Futsal Shooting Skill Levels in the Extracurricular Program at SMPN 12 Kota Bengkulu - Prasetio Alfa Rido; Rafles Ramadan; Roberto Wilson; David Andriyan Dino; Edri Alfarizi; Supriyanto Supriyanto (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aims to analyze and describe the futsal shooting skill levels of students in the extracurricular program at SMPN 12 Bengkulu City. This was a descriptive quantitative study using a survey method. The population and sample consisted of all 30 active futsal extracurricular students, selected using total sampling. The research instrument utilized a futsal shooting skill test with 10 attempts (5 with the right foot and 5 with the left foot). The data were analyzed using descriptive percentage statistics. The results indicated that the majority of students' shooting skills fell into the